2012
DOI: 10.1016/j.jembe.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Foraging ecology of five toothed whale species in the Northwest Iberian Peninsula, inferred using carbon and nitrogen isotope ratios

Abstract: International audienceThe feeding ecology and habitat use of the most frequently sighted and/or regularly reported stranded or bycaught toothed whale species of the North Western Iberian Peninsula (NWIP) were examined, with a special focus on their trophic position (TP) and relationships with their prey. With this aim, the stable isotope ratios of carbon (δ13C) and nitrogen (δ15N) of common dolphin (Delphinus delphis), bottlenose dolphin (Tursiops truncatus), harbour porpoise (Phocoena phocoena), striped dolph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 46 publications
4
54
0
Order By: Relevance
“…However, the spatial variability of δ 13 C and δ 15 N values from the base of the different food webs in the area (Chouvelon et al 2012), and also shown here with isotope values of mesozooplanktonic species, rather supports the hypothesis of more offshore feeding habits for anchovies than the hypothesis of a lower trophic level. Anchovies would effectively be able to capture larger particles than sardines (Louw et al 1998;Van der Lingen et al 2006), thanks to differences in gill raker morphology between both species and the existence of a larger branchial apparatus in anchovies (James and Findlay 1989).…”
Section: Linking Resource Variability and Feeding Patterns Of Sardinesupporting
confidence: 65%
See 1 more Smart Citation
“…However, the spatial variability of δ 13 C and δ 15 N values from the base of the different food webs in the area (Chouvelon et al 2012), and also shown here with isotope values of mesozooplanktonic species, rather supports the hypothesis of more offshore feeding habits for anchovies than the hypothesis of a lower trophic level. Anchovies would effectively be able to capture larger particles than sardines (Louw et al 1998;Van der Lingen et al 2006), thanks to differences in gill raker morphology between both species and the existence of a larger branchial apparatus in anchovies (James and Findlay 1989).…”
Section: Linking Resource Variability and Feeding Patterns Of Sardinesupporting
confidence: 65%
“…In autumn 2011, the spread of isotope values for anchovies was relatively large. Chouvelon et al (2012) ). In autumn, abundances of mesozooplankton may effectively stay at levels that anyway sustain energetic needs of both species and other plankton feeders.…”
Section: Linking Resource Variability and Feeding Patterns Of Sardinementioning
confidence: 99%
“…13,no. 4 inshore to offshore areas (France 1995, Clementz & Koch 2001, Kurle & Gudmundson 2007, Cherel & Hobson 2007, Newsome et al 2010, Ohizumi & Nobuyuki 2010, Gibbs et al 2011, Méndez-Fernandez et al 2012. Based on these constraints, a future line of investigation could apply molecular tracers to more accurately identify the ecological niches of these animals (Fernández et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases competing marine predators coexist in the same habitat because they segregate in the exploitation of trophic resources (Albo-Puigserver et al, 2015;Linke et al, 2001;Mèndez-Fernandez et al, 2012;Romeo et al, 2009). For this reason, little tunny and Atlantic bonito probably segregate their main trophic resources as a mechanism allowing their coexistence in the pelagic habitat.…”
Section: Although the Presence Of Fin-fish In The Diet Of Swordfish Imentioning
confidence: 99%